2016
DOI: 10.1016/j.mssp.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

First principles insights into improved catalytic performance of BaTiO3- graphene nanocomposites in conjugation with experimental investigations

Abstract: The present work aims to provide first principles insights into the catalytic performance of composites based on BaTiO 3 particles decorated over reduced graphene oxide (rGO).Examination regarding the orbital contributions of valence states, conduction states, interaction surface and anchoring of perovskite over rGO have been carried out. Theoretical results thus obtained have been validated using experimental investigation. Further experiments have also been conducted to analyze the catalytic performance of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Therefore, pure BiFeO 3 can perform only the second redox reaction of RhB degradation since it has VBM > 2.38 V and CBM > −0.16 V. Infusion of rGO influences the valence and conduction band structure of the pure BiFeO 3 and Bi 25 FeO 40 nanoparticles. Introduction of C 2p orbital of rGO causes both valence and conduction band potentials to raise upward as shown in a previous first-principle investigation on BaTiO 3 -rGO composite 75 . We propose that similar interactions may have taken place in the BiFeO 3 -rGO and Bi 25 FeO 40 -rGO nanocomposites.…”
Section: Resultsmentioning
confidence: 62%
“…Therefore, pure BiFeO 3 can perform only the second redox reaction of RhB degradation since it has VBM > 2.38 V and CBM > −0.16 V. Infusion of rGO influences the valence and conduction band structure of the pure BiFeO 3 and Bi 25 FeO 40 nanoparticles. Introduction of C 2p orbital of rGO causes both valence and conduction band potentials to raise upward as shown in a previous first-principle investigation on BaTiO 3 -rGO composite 75 . We propose that similar interactions may have taken place in the BiFeO 3 -rGO and Bi 25 FeO 40 -rGO nanocomposites.…”
Section: Resultsmentioning
confidence: 62%
“…The achieved results by sonophotocatalysis are very promising and remarkably higher than those previously reported for RhB degradation [ 36 ]. Ahmad et al [ 21 ] actually reported an increase of the sonophotocatalytic kinetic rate constant of only 4 times and 3 times, with respect to the individual photocatalytic and sonocatalytic processes, respectively, carried out with ZnO/CNTs composites.…”
Section: Resultsmentioning
confidence: 79%
“…Another intriguing method to enhance the e À /h + spatial separation is to decorate electron traps onto the semiconductor photocatalysts. [12][13][14][15][16] The most important electron traps include graphene, carbon nanofibers/nanotubes/quantum dots and noble metal nanoparticles. These nanosized carbon and noble metal materials are particularly interesting and have received much attention due to their fascinating physical properties and potential technological applications in many fields.…”
Section: Introductionmentioning
confidence: 99%